2016
DOI: 10.4103/1305-7456.195165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma concentrations on the proliferation of periodontal cells: An in vitro study

Abstract: Objective:The purpose of this study was to evaluate the effect of different concentrations of platelet-rich plasma (PRP) on the proliferation of undifferentiated periodontal ligament (PDL) fibroblasts.Materials and Methods:The undifferentiated PDL fibroblasts were obtained from two healthy human premolar teeth and cultured in Dulbecco's modified Eagle's medium. Cell wells were divided into five groups. Experimental groups received 0.1%, 5%, or 50% PRP; the positive and negative control groups were cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…In the present study, a novel papillary augmentation access was proposed where both buccal and palatal tunneling was performed with the placement of CTG and PRF [22][23][24][25] as matrices, and the papilla being displaced as a gingivopapillary unit.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a novel papillary augmentation access was proposed where both buccal and palatal tunneling was performed with the placement of CTG and PRF [22][23][24][25] as matrices, and the papilla being displaced as a gingivopapillary unit.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 10% PRP to the culture medium stimulated more mitogenic response in PDL cells than the addition of 5% PRP; however, this difference was not statistically significant. From a previous study,[ 7 ] 5% PRP had a greater stimulating impact on cellular proliferation but 50% PRP adversely affected cell vitality. Creeper et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that PRP could stimulate PDL fibroblast proliferation. [ 7 ] However, the regenerative events also require migration and attachment of connective tissue cells to the wound site and synthesis of the specialized components which they are attempting to repair. Thus, the aim of this study was to evaluate the effects of PRP on the proliferation, migration, and attachment of PDL cells in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 10% PRP to the culture medium stimulated more mitogenic response in PDL cells than the addition of 5% PRP; however, this difference was not statistically significant. From a previous study, [7] 5% PRP had a greater stimulating impact on cellular proliferation but 50% PRP adversely affected cell vitality. Creeper et al [20] reported a cytotoxic effect of 100% PRP.…”
Section: Discussionmentioning
confidence: 79%